2016
DOI: 10.1039/c5ee03858h
|View full text |Cite
|
Sign up to set email alerts
|

A perspective on low-temperature solid oxide fuel cells

Abstract: This article provides a perspective review of low-temperature solid oxide fuel cells research and development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
467
1
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 799 publications
(488 citation statements)
references
References 498 publications
10
467
1
10
Order By: Relevance
“…As the cathode reaction only take place at the three-phase boundary (TPB) sites where LSM-YSZ-gas phase meeting together, the microstructure design is an important process to increase the TPB sites from larger active sites and better connectivity for optimizing the cathode electrochemical reaction. [13][14][15] Many efforts have been made to optimize the microstructure of the cathode in order to gain an satisfied polarization resistance by changing various mixed ion/electron conductors, [16][17] production methods (infiltration, impregnation), [18][19][20] preparation conditions (temperature, time , etc), 21 and material morphology (particle size and shape).…”
Section: Introductionmentioning
confidence: 99%
“…As the cathode reaction only take place at the three-phase boundary (TPB) sites where LSM-YSZ-gas phase meeting together, the microstructure design is an important process to increase the TPB sites from larger active sites and better connectivity for optimizing the cathode electrochemical reaction. [13][14][15] Many efforts have been made to optimize the microstructure of the cathode in order to gain an satisfied polarization resistance by changing various mixed ion/electron conductors, [16][17] production methods (infiltration, impregnation), [18][19][20] preparation conditions (temperature, time , etc), 21 and material morphology (particle size and shape).…”
Section: Introductionmentioning
confidence: 99%
“…For the case of thin film La 0.6 Sr 0.4 CoO 3-δ (LSC), performance degradation was observed upon coating Co 3 O 4 by atomic layer deposition (ALD). 32,33 We believe that these controversies arise 4 NPs have a high intrinsic ORR activity, but this activity is subject to fast coarsening at elevated temperatures.…”
Section: R P Vs Sr/co Ratio In Sc-infiltrated Gdc (Sc-gdc) Cathodes-mentioning
confidence: 99%
“…[4][5][6] It has been reported that the lattice parameters of these structures can be tuned to yield high mixed electronic/ionic conductivity and high concentration of oxygen vacancies on the surface, two of which are the important descriptors of high ORR activity.…”
mentioning
confidence: 99%
“…1 However, lowering the temperature slows the kinetics of the thermally activated mechanisms that dominate most SOFC processes. Thus, there is a substantial ongoing research effort to identify new materials, especially cathode materials, that can maintain device performance, at intermediate temperature.…”
mentioning
confidence: 99%
“…Thus, there is a substantial ongoing research effort to identify new materials, especially cathode materials, that can maintain device performance, at intermediate temperature. 1 One of the most time-consuming steps in identifying new materials is the characterization of their oxygen transport kinetic properties, and associated sample preparation. For electronically-conducting electrodes, the three phase boundary (TPB) linear-specific resistance is usually measured.…”
mentioning
confidence: 99%